Elevated cardiac troponin T is associated with increased left ventricular mass index and predicts mortality in continuous ambulatory peritoneal dialysis patients - TOKAY TARHAN, SENA (OXFORD UNIV PRESS, 2005)
Background. Patients with end-stage renal disease have a high risk of premature death, which is due mainly to cardiovascular (CV) events. Elevated cardiac troponin T (cTnT) is related to increased left ventricular mass index (LVMI) and predicts poor outcome in chronic haemodialysis patients. We investigated the prognostic value of cTnT and its relationship with left ventricular mass in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods. Sixty-five CAPD patients (mean age: 56 +/- 12 years; 36% males) with no evidence of acute coronary syndrome in 28 days prior to the study were examined prospectively. After 48 months of follow-up, we evaluated total and CV mortality. Results. During follow-up, 23 patients (35%) died (70% CV causes, 22% infection, 4% tumour, 4% unknown). In univariate analysis, concentrations of cTnT >= 0.035ng/ml, increased LVMI, diabetes, serum albumin and age were all strong predictors of total mortality. In multivariate logistic regression analysis, cTnT >= 0.035ng/ml and age independently predicted total mortality [odds ratio (OR): 4.31; 95% confidence interval (95% CI): 1.16-16.04; P=0.008 and OR: 1.08; 95% CI: 1.02-1.15; P=0.002, respectively]. cTnT level >= 0.035ng/ml was the only independent predictor of CV mortality in multivariate logistic regression analysis (OR: 8.94; 95% CI: 2.23-35.88; P < 0.005). There was a significant positive correlation between serum cTnT level and LVMI (rho=0.41; P < 0.002). Neither cTnI, CK nor CK-MB were related to total or CV mortality. Conclusions. Elevated serum cTnT but not cTnI predicted total and CV mortality in CAPD patients. Elevated cTnT levels were also associated with increased LVMI.
Keywords: continuous ambulatory peritoneal dialysis; left ventricular hypertrophy; survival; troponin; DISEASE; EXPRESSION; HEMODIALYSIS; ISOFORMS